2019
DOI: 10.1038/s41598-019-40966-z
|View full text |Cite
|
Sign up to set email alerts
|

The MurG glycosyltransferase provides an oligomeric scaffold for the cytoplasmic steps of peptidoglycan biosynthesis in the human pathogen Bordetella pertussis

Abstract: Peptidoglycan is a major component of the bacterial cell wall and thus a major determinant of cell shape. Its biosynthesis is initiated by several sequential reactions catalyzed by cytoplasmic Mur enzymes. Mur ligases (MurC, -D, -E, and -F) are essential for bacteria, metabolize molecules not present in eukaryotes, and are structurally and biochemically tractable. However, although many Mur inhibitors have been developed, few have shown promising antibacterial activity, prompting the hypothesis that within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…4A). MurG has been shown to act as a scaffold for PG biosynthesis in Bordetella pertussis and Thermotoga maritima (64,65) and could provide a similar function in C. crescentus, though it remains unclear if the changes we observe for MurG are due to absence of a direct interaction with GroESL, or perhaps loss of an upstream signal required for PG biosynthetic subcomplex assembly. Depletion of PG precursors, which may occur through a reduction in pathway protein function, results in filamentation to conserve limited resources and prevent overinvestment in the intensive process of building new cell poles (51).…”
Section: Discussionmentioning
confidence: 89%
“…4A). MurG has been shown to act as a scaffold for PG biosynthesis in Bordetella pertussis and Thermotoga maritima (64,65) and could provide a similar function in C. crescentus, though it remains unclear if the changes we observe for MurG are due to absence of a direct interaction with GroESL, or perhaps loss of an upstream signal required for PG biosynthetic subcomplex assembly. Depletion of PG precursors, which may occur through a reduction in pathway protein function, results in filamentation to conserve limited resources and prevent overinvestment in the intensive process of building new cell poles (51).…”
Section: Discussionmentioning
confidence: 89%
“…Although structural studies have provided no direct evidence, a highly oligomeric state of MurG has consistently been proposed as a functional unit by biochemical, biophysical and cellular studies (Laddomada et al, 2019;Ha et al, 1999).…”
Section: Abmurg Forms Hexameric Homo-oligomeric Complex Structuresmentioning
confidence: 99%
“…Owing to the critical activity of MurG in bacterial cell-wall synthesis and its attractiveness as an antibiotic target, structural and biochemical studies have been performed in order to understand its molecular mechanism (Ha et al, 1999;Mohammadi et al, 2007;van den Brink-van der Laan et al, 2003;Hu et al, 2004). Although previous studies of Escherichia coli MurG (ecMurG) have shown how MurG functions in the membrane and how its active site recognizes substrates (Ha et al, 2000;Hu et al, 2003), the molecular mechanism of the oligomeric scaffolding assembly of MurG, as identified in several bacterial species in recent studies (Laddomada et al, 2019), has remained unclear. This study characterized MurG from A. baumannii (abMurG).…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggests that MurG solubility and localization may also respond to GroESL-mediated folding ( Figure 4A). MurG has been shown to act as a scaffold for PG biosynthesis in Bordetella pertussis and Thermotoga maritima (63,64) processes are protected during high unfolding demand. Discerning these interactions will be important to understanding how organisms balance growth and division when surviving stress.…”
Section: Crescentus and Has Identified Several New Interactions Betwmentioning
confidence: 99%